Replica-exchange optimization of antibody fragments. (April 2023) - Soler, Miguel A.; Minovski, Nikola; Rocchia, Walter; Fortuna, Sara
Abstract: In the framework of the rational design of macromolecules capable of binding to a specific target for biosensing applications, we here further develop an evolutionary protocol designed to optimize the binding affinity of protein binders. In particular we focus on the optimization of the binding portion of small antibody fragments known as nanobodies (or VHH) and choose the hen egg white lysozyme (HEWL) as our target. By implementing a replica exchange scheme for this optimization, we show that an initial hit is not needed and similar solutions can be found by either optimizing an already known anti-HEWL VHH or a randomly selected binder (here a VHH selective towards another macromolecule). While we believe that exhaustive searches of the mutation space are most appropriate when only few key residues have to be optimized, in case a lead binder is not available the proposed evolutionary algorithm should be instead the method of choice. Graphical Abstract: ga1 Highlights: We here further develop an evolutionary protocol for binding affinity optimisation. We implement a replica exchange scheme for antibody fragments optimisation. We show that an initial hit is not needed. Similar solutions can be found by either optimizing a known weak binder or a non-binder.